LINEAR PROGRAM MODEL FOR PROFIT OPTIMIZATION IN MEATBALL SALES USING GRAPH METHOD - Hasanah Tri Amisri, Nurul; Tribuana Citra, Indah; Hafizah Siregar3, Anisa; Aprilia, Tria Aprilia (Pena Cendekia Insani, 2023)
The production process is an important thing that can affect profits. The production process also needs to be considered to increase profits to be more optimal. This optimization problem is still an obstacle for most businesses, one of which is the sale of meatballs with the owner of Bakso Bang Riski and Tante Juli located on Jl. Lapangan Golf Tuntungan.This study aims to optimize profits on meatball sales through the application of linear program models with the graph method. In the sale of meatballs studied using meat and flour raw materials to produce 200 servings of meatballs per day with a price per serving of Rp. 5000 and an average income of Rp. 200,000 per day. This research uses a qualitative approach with descriptive analysis, developing mathematical models in the form of decision variables, objective functions, and constraint functions. The analysis results show that the graph method is effective in maximizing profits, with a maximum income of Rp4,000,000 per month and a profit of Rp3,800,000 or 80% of the total initial income. This method provides a practical solution for MSME players to improve production efficiency and business profits through a mathematical approach